Analisis Perilaku Petugas Kesehatan Terhadap Penanganan Limbah Medis Tajam Di Rumah Sakit Ernaldi Bahar Provinsi Sumatera Selatan Tahun 2023 - Devie Sandria; Ali Harokan; Arie Wahyudi (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2023)
The World Health Organization (WHO) estimates that around 16 billion needle sticks are used worldwide each year, if safety precautions are not followed, the risk of injury from sharps increases among paramedics. This study aims to determine the factors related to the behavior of health workers towards the handling of sharp waste at the Ernaldi Bahar Hospital, South Sumatra Province 2023. The design of this study was quantitative with a cross sectional approach. The population in this study were all health workers who handled sharp waste as many as 169 respondents using the Total Sampling technique. The sample in this study was 169 people. This research was carried out from 18 May 2023 to 29 May 2023. Data collection used a questionnaire. Bivariate data analysis using the Chi-Square test. The results showed that there was a relationship between knowledge (p value 0.010), attitude (p value 0.005), training (p value 0.010) towards Sharp Medical Waste Handling at Ernaldi Bahar Hospital, South Sumatra Province in 2023. There was no relationship between age (p value 0, 76), gender (p value 0.44), education (p value 0.86) and years of service (p value 0.161) on the Handling of Sharp Medical Waste at Ernaldi Bahar Hospital, South Sumatra Province in 2023. The conclusion is that there is a relationship between knowledge, attitudes and training, there is no relationship between age, gender, education and years of service for handling sharp medical waste at Ernaldi Bahar Hospital, South Sumatra Province in 2023. There is a need for continuous planning and training